2007
DOI: 10.1590/s1413-86702007000200010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of respiratory infections by influenza viruses A and B in pediatrics patients from Federal University of Paraná, Brazil

Abstract: The objective of the present study was to determine the impact of influenza virus on pediatric hospitalized patients. We retrospectively reviewed records of children with laboratory diagnoses, by cell culture and/or indirect immunofluorescence assay, of influenza virus seen in a period of 6 years. A total of 1,033 samples were analyzed, 45 (4.3%) of them being reactive to influenza virus. Thirty-one samples were positive to influenza A virus and 14 to influenza B. The frequency of hospitalization in intensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 22 publications
0
12
0
4
Order By: Relevance
“…The proportion of confirmed influenza in ILI cases was high in children aged 5–14 years, while in children younger than 5 years and older than 14 years the proportion of confirmed influenza in ILI cases was low. Meta‐analysis of the proportion of confirmed influenza in LRTI reported in 16 studies 2,55,60–83 showed that the highest proportion occurred in the adolescent population. Type A was more prevalent than type B in confirmed cases of ILI and LRTI (Table 8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of confirmed influenza in ILI cases was high in children aged 5–14 years, while in children younger than 5 years and older than 14 years the proportion of confirmed influenza in ILI cases was low. Meta‐analysis of the proportion of confirmed influenza in LRTI reported in 16 studies 2,55,60–83 showed that the highest proportion occurred in the adolescent population. Type A was more prevalent than type B in confirmed cases of ILI and LRTI (Table 8).…”
Section: Resultsmentioning
confidence: 99%
“…Influenza virus is a highly contagious etiological agent that spreads rapidly and causes an acute respiratory illness, mostly characterized by sudden onset of high fever, myalgia, headache, sore throat, and inflammation 1,2 . It is usually self‐limited, and the patient recovers within 1 or 2 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Such wide variability may be explained by differences in the rate of the complications studied, the diversity of infl uenza viruses involved in the seasons analysed and differences in hospitals' infection management protocols (14)(15)(16)(17). It is most likely that many differences between studies were due to the strains' virulence being different since the same strain can circulate for several consecutive years and therefore be associated with being benign or more tables associated with more severe disease, thereby signifi cantly changing their antigenic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Nas infecções virais do trato respiratório, primeiramente observam-se sintomas de infecção das vias aéreas superiores apresentando sintomas como um simples resfriado caracterizado por febre, tosse e coriza, porém devido à afinidade viral por órgãos respiratórios inferiores, estas infecções evoluem para o trato respiratório inferior, apresentando quadros clínicos mais severos como bronquite, bronquiolite, broncopneumonia, insuficiência respiratória aguda e pneumonia (COELHO et al, 2007 Além disso, novos subtipos de Rhinovírus têm sido recentemente identificados (LAMSON et al, 2006;MCERLEAN et al, 2008), evidenciando a diversidade desses vírus e a habilidade de escapar da resposta imune pré-existente.…”
Section: -Sintomatologiaunclassified
“…Mas, apesar de existir uma vacina de prevenção contra esse vírus e muitas infecções causadas por ele poderem ser prevenidas com um programa de vacinação efetivo, uma pequena variação no antígeno pode fazer com que a vacina atual não seja mais eficaz, sendo assim necessária uma constante vigilância epidemiológica (COELHO et al, 2007).…”
Section: -Diagnóstico Tratamento E Prevençãounclassified